Back spin - Coben, Harlan, 1962- (Dell Publishing, 2011)
The boy was born and raised on the tony Main Line. But he vanished on Philadelphia's mean streets. For Myron Bolitar, his client, golf superstar Linda Coldren, comes first--and that means unraveling the mystery of her son's kidnapping. But when Myron goes after the missing boy, he crashes through a crowd of lowlifes, blue bloods, and liars on both sides of the social divide. And as Linda's golf-pro husband suddenly makes a run at the U.S. Open championship, the family's skeletons burst out of the closet. Myron is about to find out just how deadly this game can get. The fourth in the Myron Bolitar series.
Keywords: Bolitar, Myron -- (Fictitious character); Missing children -- Fiction; Sports agents -- Fiction; Golfers -- Fiction; Kidnapping -- Fiction; Philadelphia (Pa.) -- Fiction; Golf stories; Detective and mystery fiction